A STRUKTUR DAN ANATOMI ORGANISASI DALAM PENDIDIKAN ISLAM: STRUKTUR DAN ANATOMI ORGANISASI DALAM PENDIDIKAN ISLAM - Buya Riadi; maskin; Kasinyo Harto; Tutut Handayani (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
This paper systematically discusses the structure and anatomy of organizations as fundamental elements in understanding how an organization functions and adapts to its internal and external environments. This research is descriptive-analytical in nature with a qualitative approach, aiming to identify the relationship between organizational structure design, division of tasks, hierarchy of authority, and coordination mechanisms that support organizational performance effectiveness. The results of the study show that organizational structure not only reflects the formal patterns of division of labor and responsibilities, but also describes the dynamics of communication and decision-making within the organization. Organizational anatomy includes key elements such as objectives, human resources, technology, and managerial systems that interact with each other in achieving the strategic vision. The theoretical study is based on classical and modern perspectives, including Max Weber's bureaucracy theory, contingency theory, and the open system approach that emphasizes flexibility and adaptation. Empirically, this paper asserts that organizational effectiveness is highly dependent on the alignment between formal structure and work culture that supports collaboration and innovation. Thus, a deep understanding of organizational structure and anatomy is an important basis in the process of strategic planning, organizational change, and continuous performance improvement.